Pembelajaran Berbasis Masalah: Pengoptimalan Media Online Melalui Pembelajaran Berjarak - Heri Bayu Dwi Prabowo (Proceedings Series on Social Sciences & Humanities, 2021)
The world is being rocked by the covid-19 pandemic outbre ak. The pandemic effect on all human activities as a whole, whitout exception the education world. Education as an one of the heart of the nation’s solid survival must be save under these conditions, including education in Indonesia. Since the implementation of learning at home by the goverment on March, 16, 2020, learning patterns have changed in such a way. The question is, what kind of learning is effective in the present? In this case, the problem to be answered will be examined with the idea of distance learning (PJJ) through online media in an effort to keep the learning and learning process going. This research uses library research, while the source of data is obtained through a variety of relevant literature. In this case, the researcher uses theory of problem based learning and distance learning. As a result, the learning process at this time still needs to be intensively studied, improved and further developed. In addition, improving the format of education is a shared responsibility of all elements of society, working hand in hand and supporting the resilience and effectiveness of learning at all levels of education is a necessity.